Women's work in the unorganised sector : issues of exploitation and globalisation in the beedi industry - Pande, Rekha, 1955- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book probes into the beedi industry, a highly gendered and class-divided unorganised sector in India. It introduces an analysis of the lives, health status and work of the Indian women and girl children in the industry and discusses the role of gender constructions, global capitalism, and global racism in shaping the ideologies and conceptions about men and women at work. The volume presents a gendered postcolonial perspective on women's employment in the context of social and economic processes that are critical to globalization. It focuses on Telangana's Nizamabad district - where a majority of the women population are employed in the beedi industry. Through detailed surveys and case studies, the author analyses different aspects of exploitation of these women such as poor working conditions, income inequalities, health risks and the realities of child labour in the process of beedi making. Richly detailed, this book will be of great interest to students, researchers and teachers of geography, particularly human geography and feminist geography, women and gender studies, feminism, labour economics, capitalism, development studies, political sociology, and cultural studies. It will also be of interest to gender and feminist geographers, occupational health professionals, NGOs, and those interested in the issues of gender and development"--
The beedi industry : structure and organization -- Women's work in the unorganised sectors : issues of marginalisation and globalisation -- Child work and child labour -- Anti-tobacco history and control -- The region : the field -- The beedi worker : socio economic profile -- Beedi making at home and at the work shed -- Invisible labour : the girl child worker -- Beedi making, health and disease -- Narratives of vulnerability and exploitation -- Conclusions and the way forward.
Keywords: Women tobacco workers -- India -- Nizamabad (District) -- Social conditions; Tobacco industry -- India -- Nizamabad (District); Child labor -- India -- Nizamabad (District); SOCIAL SCIENCE / General; SOCIAL SCIENCE / Human Geography; SOCIAL SCIENCE / Women's Studies